Detecting proteinuria: A comparison of diagnostic tests - Jeanida Mauliddina; Rosmayanti Siregar; Oke Rina Ramayani; Rafita Ramayati; Rusdidjas Rusdidjas (Paediatrica Indonesiana, 2011)
Background Proteinuria is a condition when protein is found in urine, a common symptom in children with renal disorders. Proteinuria can also be found in nonnal children and in those with non-renal disorders. A high sensitivity test is needed to detect proteinuria. Spectrophotometry has been used as a standard to detect proteinuria, however, it is expensive and not readily available in health clinics. We tested the use of20% sulfosalicylic add to detect proteinuria, and compared it to spectrophotometry. The sulfosalicylic add test is inexpensive, rapid, and easily performed in primary community health centers.Objective To compare 2 0 % sulfosalicylic acid test t o spectrophotometry as a diagnostic test for proteinuria.Methods We conducted a cross-sectional study in Adam Malik Hospital from September 2009 until December 2009. Inclusion criteria were children aged 3 to 18 years who experienced kidney disease. We collected 24 hour urine specimens from 55 children by consecutive sampling. Urine specimens were tested for proteinuria by 20% sulfosalicylic acid test and spectrophotometry.Results Sensitivity and specificity of 20% sulfosalicylic acid test compared to spectrophotometry were 88.1 % and 69.2%, respectively, with a positive predictive value and a negative predictive value of 90.2% and 64.3%, respectively.Conclusion The sulfosalicylic acid test had low sensitivity and specificity for detecting proteinuria, but it was more practical and less expensive compared to spectrophotometry.